Bridging the Ambition Gap in Climate Policy: The Emissions Reduction Potential of Bilateral Emissions Trading Under Article 6.2 of the Paris Agreement - Christoph Böhringer; Carsten Helm; Laura Schürer (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Countries' current Nationally Determined Contributions (NDCs) under the Paris Agreement leave a substantial gap to the emissions reductions needed to limit global warming to 2°C. Böhringer et al. (2025) showed the large emissions reduction potential of global emissions trading even if countries choose their tradable emissions reduction contributions strategically as mutual bestresponse strategies. However, the prospects for a global trading system appear rather bleak. By contrast, countries have already started to trade emissions reductions in bilateral agreements under Article 6.2 of the Paris Agreement. Even though bilateral agreements may appear to be a significant restriction at first glance, they prove to be quite effective in terms of global emissions reductions when strategic choices of tradable emissions reduction contributions are taken into account. Numerical simulations based on empirical data show that the most effective bilateral trading club – consisting of South Korea or Europe and China – increases global emissions abatement from 17% (relative to BaU) without trading to 30%, and exploits 80% of the emissions reduction potential of a global trading system.
Keywords: H23; Q54; Q56; Q58; C72; 330; Paris Agreement; Article 6; emissions trading; NDCs